ANALISIS CIRI KEWIRAUSAHAAN DAN PERILAKU TERHADAP MOTIVASI BELAJAR MAHASISWA PROGRAM PENDIDIKAN EKONOMI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS TERBUKA - Suripto Suripto (Jurnal Ilmiah Econosains, 2013)
AbstractThe results showed that: (1) There is significant effect of entrepreneurial characteristics on student learning motivation; meaning the better the entrepreneurial traits will affect student learning motivation higher. (2) There is significant effect of entrepreneurial characteristics on student learning motivation; meaning the better the behavior will affect student learning motivation higher. (3) There is significant influence entrepreneurial trait and behaviors to motivate student learning; meaning the better the entrepreneurial traits and behaviors will affect student learning motivation higher.Keywords: Entrepreneurship Characteristics, Behavior, Learning Motivation.